Beginning Oracle SQL - Haan, Lex De (Apress, 2014)
Beginning Oracle SQL is your introduction to the interactive query tools and specific dialect of SQL used with Oracle Database. These tools include SQL*Plus and SQL Developer. SQL*Plus is the one tool any Oracle developer or database administrator can always count on, and it is widely used in creating scripts to automate routine tasks. SQL Developer is a powerful, graphical environment for developing and debugging queries. Oracle's is possibly the most valuable dialect of SQL from a career standpoint. Oracle's database engine is widely used in corporate environments worldwide. It is also found in many government applications. Oracle SQL implements many features not found in competing products. No developer or DBA working with Oracle can afford to be without knowledge of these features and how they work, because of the performance and expressiveness they bring to the table. Written in an easygoing and example-based style, Beginning Oracle SQL is the book that will get you started down the path to successfully writing SQL statements and getting results from Oracle Database. Takes an example-based approach, with clear and authoritative explanations Introduces both SQL and the query tools used to execute SQL statements Shows how to create tables, populate them with data, and then query that data to generate business results